ChemInform Abstract: Ring Expansion of 3‐Oxetanone‐Derived Spirocycles: Facile Synthesis of Saturated Nitrogen Heterocycles. Issue 14 (8th April 2014) - Ruider, Stefan A.; Mueller, Steffen; Carreira, Erick M.
Abstract The new efficient method for the catalytic ring expansion of oxetane derivatives leads to numerous oxazine, pyrazine, and thiazine derivatives which are difficult to access otherwise.